The Influence of Organizational Justice and Motivation on Organizational Commitment: The Mediating Role of Job Satisfaction - Wahyuni, Ayu Putri; Sutarso, Yudi (JURNAL MANAJEMEN MOTIVASI, 2025)
This study analyzes the influence of organizational justice and motivation on organizational commitment with job satisfaction as a mediating variable among employees of Koperasi As-Sakinah Surabaya. A quantitative explanatory method was used involving 142 respondents, analyzed using Partial Least Square (PLS). The results show that both organizational justice and motivation significantly affect job satisfaction. Motivation directly influences organizational commitment, while organizational justice has an indirect effect through job satisfaction. These findings highlight the importance of organizational justice and motivation in fostering employee commitment.